The MU chip - Isaacs, Andrew M., (SAGE Knowledge. Cases., 2017)
Mu Chip was a breakthrough in semiconductor technology, a microscopic chip that involves tags that emit radio signals that devices called readers can pick up. The Mu Chip could be used, for example, to integrate the chip into clothing labels so that when a customer buys a pair of jeans, that information was sent to the company's database. Expensive brands could put the Mu Chips in their products to hinder counterfeit products. The announcement of the Mu Chip had made a big splash, and more than 900 companies had expressed interest in incorporating the Mu Chips innovative technology into their products. Most of these prospects were Japanese companies, but many were multinational firms, with European or U.S. headquarters. The biggest problem now was deciding which prospects and which applications made the most sense for the new company to pursue.